Rubber resistant to lubricating medium of steam turbine generator for nuclear power and preparation method of rubber
By using rubber of specific composition in sealed tile rubber strips in nuclear power plant steam turbine generators, and forming a mesh molecular structure through pressurized heating mixing and multiple thin-pass treatments, the porosity, fracture and swelling of sealed tile rubber strips under hydrogen, non-polar solvents and other substances is solved, and better hydrogen, oil resistance and service life are achieved.
Patent Information
- Application Number
- CN202411332566.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-03-11
AI Technical Summary
The sealing tile rubber strips of nuclear power plant turbine generators are prone to poreization, fracture and swelling under the permeation of hydrogen, non-polar solvents and other substances, resulting in a decrease in sealing performance and shortening of service life.
A rubber composed of hydrogenated nitrile, vulcanizing active agent, stearic acid, anti-aging agent, plasticizer, wear-resistant agent, silane coupling agent, vulcanizing agent, promoter, ultrashort aramid fiber and alkylphenol resin is used to form a mesh molecular structure to prevent the infiltration of the medium by pressurized heating and multiple thin-pass treatments.
It improves the hydrogen and oil resistance of rubber, avoids porosity, fracture and swelling, extends the service life of sealing tiles, and enhances sealing performance.
Smart Images

Figure CN119591955A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of special rubbers and relates to a rubber resistant to lubricating medium of a steam turbine generator for nuclear power and a preparation method thereof. Background Art
[0002] In the field of modern nuclear power energy, steam turbine generators are the core power conversion devices in nuclear power plants. Their operating efficiency and stability are directly related to the power generation capacity and safety performance of the entire power plant. In order to effectively manage the large amount of heat generated by high-speed rotation and electromagnetic effects inside the generator and to ensure that the generator components are protected from high-temperature damage, hydrogen is widely used as a cooling medium. With its excellent thermal conductivity and low viscosity, hydrogen is an ideal choice for efficient cooling of generator rotor windings and stators. However, this design also brings new technical challenges, especially in the design and maintenance of the generator shaft end sealing system.
[0003] The core component of the generator shaft end sealing system in a nuclear power plant is the sealing tile, which undertakes the key task of preventing hydrogen from leaking to the outside of the generator. The sealing tile fits tightly into the tiny gap between the generator shaft and the sealing seat through the precision rubber strip embedded inside it, forming an effective hydrogen barrier. However, in actual operation, due to the high permeability of hydrogen itself and the complex influence of non-polar solvents, fuel oil, mineral oil and other substances that may exist in the nuclear power plant environment, these sealing strips are exposed to harsh environments for a long time and are prone to changes in physical and chemical properties. Specifically, after continuous penetration of substances such as hydrogen and non-polar solvents, the sealing strips will show significant swelling, that is, the volume of the material expands abnormally, resulting in an increase in the sealing gap and a significant decrease in sealing performance. At the same time, these chemicals may also cause the shrinkage and embrittlement of the strip material, further weakening its sealing effect. These adverse changes not only shorten the service life of the sealing tile, which is generally lower than the industry's expected 18-month operating cycle, but also cause a large amount of sealing oil to leak into the generator. The intrusion of sealing oil not only aggravates the pollution inside the generator, but also may cause electrical failures, and in severe cases even force the power plant to shut down urgently, which has a huge impact on the stability and economic benefits of the power grid. Therefore, in view of the severe challenges faced by the sealing strips of steam turbine generators in nuclear power plants, the development of a new type of hydrogen-resistant, oil-resistant, and long-life sealing material has become a key issue in improving the safety and efficiency of nuclear power plant operations. Summary of the invention
[0004] The purpose of the present invention is to provide a rubber that meets the technical requirements of nuclear power and is resistant to lubricating media of steam turbine generators for nuclear power, so as to solve the technical problem that the rubber that is resistant to lubricating media of steam turbine generators for nuclear power is prone to porosity, fracture and swelling during use due to the penetration of substances such as hydrogen, non-polar solvents, fuel oil and mineral oil.
[0005] Based on the above purpose, the present invention provides a rubber resistant to lubricating medium of steam turbine generator for nuclear power and a preparation method thereof to meet the needs in the art.
[0006] On the one hand, the present invention relates to a rubber resistant to lubricating medium of steam turbine generator for nuclear power, wherein the raw materials for preparing the rubber are composed of hydrogenated nitrile, vulcanization activator, stearic acid, antioxidant, plasticizer, wear resistance agent, silane coupling agent, vulcanizing agent, accelerator, ultra-short aramid fiber and alkyl phenolic resin.
[0007] Furthermore, in the rubber resistant to lubricating medium of steam turbine generator for nuclear power provided by the present invention, the raw materials for preparing the rubber are composed, by weight, of 100 parts of hydrogenated nitrile, 2 to 12 parts of vulcanization activator, 0.5 to 2 parts of stearic acid, 0.5 to 4 parts of antioxidant, 2 to 10 parts of plasticizer, 5 to 25 parts of wear resistance, 0.5 to 2 parts of silane coupling agent, 4 to 10 parts of vulcanizer, 0.8 to 2.5 parts of accelerator, 0.5 to 4 parts of ultra-short aramid fiber and 0.5 to 3 parts of alkyl phenolic resin.
[0008] Furthermore, in the rubber resistant to lubricating medium of steam turbine generator for nuclear power provided by the present invention, the length of the ultra-short aramid fiber is not more than 3 mm.
[0009] Furthermore, in the rubber resistant to lubricating medium of steam turbine generator for nuclear power provided by the present invention, the ultra-short aramid fiber is surface-modified with a diterpene quinone compound.
[0010] Furthermore, in the rubber resistant to lubricating medium of steam turbine generator for nuclear power provided by the present invention, the diterpene quinone compound is tanshinone.
[0011] Furthermore, in the rubber for nuclear power resistant to steam turbine generator lubricating medium provided by the present invention, the vulcanization activator is selected from at least one of zinc oxide and magnesium oxide;
[0012] The antioxidant is selected from at least one of antioxidant MB, phenylenediamine antioxidants, and quinoline antioxidants;
[0013] The anti-wear agent is selected from at least one of carbon black, montmorillonite, aluminum hydroxide, calcium carbide and microcrystalline wax;
[0014] The silane coupling agent is selected from at least one of silane coupling agent A172, silane coupling agent A171, and silane coupling agent A151;
[0015] The vulcanizing agent is vulcanizing agent DCP;
[0016] The accelerator is TAIC.
[0017] On the other hand, the present invention relates to a method for preparing a rubber resistant to lubricating medium of a steam turbine generator for nuclear power, comprising:
[0018] The silane coupling agent, the ultra-short aramid fiber and the alkyl phenolic resin are mixed under pressure and heating to obtain a mixture;
[0019] Hydrogenated nitrile, vulcanizing activator, stearic acid, antioxidant, plasticizer, anti-wear agent, the mixture, vulcanizing agent and accelerator are sequentially added for mixing, and after multiple thin passes, the lower sheet is cooled to obtain the product.
[0020] Furthermore, in the preparation method provided by the present invention, the ultra-short aramid fibers are surface-modified with diterpene quinone compounds before being made into the mixture;
[0021] The surface modification comprises: immersing the ultra-short aramid fiber in diterpene quinone compounds, heat-treating at 40-60° C. for 6-12 hours, taking out and washing with anhydrous ethanol, and drying at room temperature.
[0022] Furthermore, in the preparation method provided by the present invention, the pressurized and heated mixing comprises: mixing the silane coupling agent, the ultra-short aramid fiber and the alkyl phenolic resin at a pressure of 0.05 to 0.5 MPa and a temperature of 90 to 120°C.
[0023] Furthermore, in the preparation method provided by the present invention, the mixing parameters are: roller temperature 60°C to 80°C, mixing roller distance 4 to 5 mm;
[0024] The parameters of the thin pass are: the thin pass roller distance is 0.5-1mm, and the thin pass is 20 times.
[0025] Through the above technical solution, the technical solution provided by the present invention has at least the following beneficial effects or advantages:
[0026] The present invention provides a rubber for nuclear power that is resistant to lubricating medium of steam turbine generators. The composition of the rubber is a mixture prepared by mixing silane coupling agent, ultra-short aramid fiber and alkylphenolic resin under pressure and heating on the basis of general nitrile rubber. In the mixture, the alkylphenolic resin is conducive to the interface infiltration and adhesion of ultra-short aramid fiber; the aramid short fiber increases the toughness and wear resistance of the product, which is beneficial to avoid creeping and damage caused by the movement of the turbine generator bearing; the silane coupling agent increases the interface adhesion of various materials and builds molecular "bond bridges", which is conducive to the uniform dispersion of the mixture before mixing and good interface infiltration. During the mixing process, the mixture is vulcanized to form a network molecule, which prevents mixed liquid media such as hydrogen, non-polar solvents, fuel oil and mineral oil from penetrating into the interior of the network macromolecule and causing pores, fractures and swelling. The present invention further uses diterpene quinone compounds to modify the surface of ultra-short aramid fiber, further enhancing the interaction between the network macromolecule and the matrix rubber, so that the network macromolecule is better filled in the matrix rubber, and better material properties are obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 The cross-sectional morphology of the rubber strip.
[0029] Figure 2 This is the cross-sectional morphology of the damaged rubber strip.
[0030] Figure 3 This is the SEM image of 11# rubber strip.
[0031] Figure 4 This is the SEM image of 3# rubber strip.
[0032] Figure 5 This is the SEM image of 5# rubber strip. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments, but the embodiments are not intended to limit the present invention.
[0034] The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the test supplies and raw materials are all commercially available unless otherwise specified.
[0035] Example 1
[0036] This embodiment provides a method for preparing a rubber resistant to lubricating medium of a steam turbine generator for nuclear power.
[0037] The raw materials are taken in parts by mass: 100 parts of hydrogenated nitrile, 1 part of vulcanizing activator (zinc oxide), 1 part of vulcanizing activator (magnesium oxide), 0.5 parts of stearic acid, 0.5 parts of antioxidant MB, 2 parts of plasticizer TP-95, 5 parts of wear-resistant agent (super wear-resistant carbon black N110), 10.5 parts of silane coupling agent A17, 4 parts of vulcanizing agent DCP, 0.8 parts of accelerator TAIC, 0.5 parts of ultra-short aramid fiber (length 1 mm) and 0.5 parts of alkyl phenolic resin.
[0038] The ultra-short aramid fiber was immersed in danshen ketone, heated to 40°C in a water bath for 6 hours, and the danshen ketone that was not fully bound to the surface was taken out and washed with anhydrous ethanol. The anhydrous ethanol was removed by drying at room temperature to obtain the surface-modified ultra-short aramid fiber.
[0039] The surface-modified ultra-short aramid fiber, alkyl phenolic resin and silane coupling agent were placed in a 10L pressure container and stirred at a temperature of 90°C, a pressure of 0.05MPa, a stirring speed of 30 rpm, and a stirring time of 4h to obtain a mixture.
[0040] 26-inch open mill, roller temperature 60℃, mixing roller distance 4mm; thin pass roller distance 0.5mm. Adding order: raw rubber (hydrogenated nitrile) → vulcanization activator, stearic acid, antioxidant, plasticizer, wear-resistant agent → mixture → vulcanizer, accelerator → thin pass 20 times → cool the lower sheet for 24 hours before use.
[0041] Example 2
[0042] This embodiment provides a method for preparing a rubber resistant to lubricating medium of a steam turbine generator for nuclear power.
[0043] The raw materials are taken in parts by mass: 100 parts of hydrogenated nitrile, 7 parts of vulcanizing activator (magnesium oxide), 1 part of stearic acid, 2 parts of antioxidant MB, 5 parts of plasticizer TP-95, 10 parts of wear-resistant agent (white carbon black), 5 parts of wear-resistant agent (montmorillonite), 1 part of wear-resistant agent (microcrystalline wax B10), 10.5 parts of silane coupling agent A171, 0.5 parts of silane coupling agent A172, 7 parts of vulcanizing agent, 1.2 parts of accelerator, 2 parts of ultra-short aramid fiber (length 3 mm) and 2 parts of alkyl phenolic resin.
[0044] The ultra-short aramid fiber was immersed in danshen ketone, heated to 50°C in a water bath for 9 hours, and the danshen ketone that was not fully bound to the surface was taken out and washed with anhydrous ethanol. The anhydrous ethanol was removed by drying at room temperature to obtain the surface-modified ultra-short aramid fiber.
[0045] The surface-modified ultra-short aramid fibers, alkyl phenolic resin and silane coupling agent were placed in a 10L pressure vessel and stirred at a temperature of 110°C, a pressure of 0.1MPa, a stirring speed of 30 rpm and a stirring time of 4h.
[0046] 26-inch open mill, roller temperature 70℃, mixing roller distance 5mm; thin pass roller distance 1mm. Adding order: raw rubber (hydrogenated nitrile) → vulcanization activator, stearic acid, antioxidant, plasticizer, wear-resistant agent → mixture → vulcanizer, accelerator → thin pass 20 times → cool the lower sheet for 24 hours before use.
[0047] Example 3
[0048] This embodiment provides a method for preparing a rubber resistant to lubricating medium of a steam turbine generator for nuclear power.
[0049] The raw materials are taken in parts by mass: 100 parts of hydrogenated nitrile, 12 parts of vulcanizing activator (zinc oxide), 2 parts of stearic acid, 1 part of antioxidant MB, 2 parts of antioxidant 4010NA, 1 part of antioxidant RD, 10 parts of plasticizer TP-95, 20 parts of wear-resistant agent (super wear-resistant carbon black N110), 5 parts of wear-resistant agent (aluminum hydroxide), 5 parts of wear-resistant agent (calcium carbide), 11 parts of silane coupling agent A17, 11 parts of silane coupling agent A15, 10 parts of vulcanizing agent DCP, 2.5 parts of accelerator TAIC, 2 parts of ultra-short aramid fiber (length 1 mm), 2 parts of ultra-short aramid fiber (length 3 mm) and 3 parts of alkyl phenolic resin.
[0050] The ultra-short aramid fiber was immersed in danshen ketone, heated to 60°C in a water bath and kept warm for 12 hours, the danshen ketone that was not fully bound to the surface was taken out and washed with anhydrous ethanol, and the anhydrous ethanol was removed by drying at room temperature to obtain the surface-modified ultra-short aramid fiber.
[0051] The surface-modified ultra-short aramid fibers, alkyl phenolic resin and silane coupling agent were placed in a 10L pressure vessel and stirred at a temperature of 120°C, a pressure of 0.5 MPa, a stirring speed of 30 rpm and a stirring time of 4 hours.
[0052] 26-inch open mill, roller temperature 80℃, mixing roller distance 5mm; thin pass roller distance 1mm. Adding order: raw rubber (hydrogenated nitrile) → vulcanization activator, stearic acid, antioxidant, plasticizer, wear-resistant agent → mixture → vulcanizer, accelerator → thin pass 20 times → cool the lower sheet for 24 hours before use.
[0053] Example 4
[0054] This embodiment is the same as Embodiment 1, except that the ultra-short aramid fibers are not surface-modified.
[0055] Example 5
[0056] This embodiment is the same as Embodiment 2, except that the ultra-short aramid fibers are not surface-modified.
[0057] Example 6
[0058] This embodiment is the same as Embodiment 3, except that the ultra-short aramid fibers are not surface-modified.
[0059] Comparative Example 1
[0060] This comparative example is intended to illustrate the effect of aramid fiber length on product performance. This comparative example is the same as Example 1, except that the ultra-short aramid fiber is replaced with aramid fiber with a length of 6 mm.
[0061] Comparative Example 2
[0062] This comparative example is intended to illustrate that the three components of silane coupling agent, ultra-short aramid fiber and alkylphenol-formaldehyde resin are indispensable. This comparative example is the same as Example 1, except that the alkylphenol-formaldehyde resin is not added.
[0063] Example 7
[0064] This embodiment provides the surface conditions of each rubber strip under simulated working conditions.
[0065] The sealing shoe of the steam turbine generator is installed on the sealing shoe chamber through a pin. It can float up and down 0.2mm, the operating temperature is about 60-90℃, the rubber strip is compressed by about 0.2mm, contacts hydrogen, and is immersed in the generator sealing oil. The sealing strip is a sealing element with a circular cross-section. It plays a sealing role after being compressed and deformed in a medium of certain temperature, pressure, fire-resistant oil and hydrogen. The sealing shoe rubber strip can reliably seal within the service life of 18 months without affecting the normal operation of the sealing shoe.
[0066] In this embodiment, the rubber strips provided with the TBB-1000-2у3 steam turbine generator produced in Russia were sampled, and the rubber strips of Examples 1 to 6 and Comparative Examples 1 to 2 were tested under simulated working conditions. The test results are as follows: Figure 1 and Figure 2 shown.
[0067] Figure 1 and Figure 2 Among them, 1# rubber strip is the rubber strip before the simulated working condition of Example 1, 2# rubber strip is the rubber strip before the simulated working condition of Example 4, 3# rubber strip is the original rubber strip taken out after the TBB-1000-2у3 steam turbine generator has been in operation for 18 months, 4# rubber strip is the original rubber strip taken out after the TBB-1000-2у3 steam turbine generator has been in operation for 2 months, 5# to 7# rubber strips are the rubber strips after the simulated working condition of Comparative Example 1, 8# to 10# rubber strips are the rubber strips after the simulated working condition of Comparative Example 2, 11# rubber strip is the rubber strip after the simulated working condition of Example 1, 12# rubber strip is the rubber strip after the simulated working condition of Example 4, 13# rubber strip is the rubber strip after the simulated working condition of Example 2, 14# rubber strip is the rubber strip after the simulated working condition of Example 5, 15# rubber strip is the rubber strip after the simulated working condition of Example 3, and 16# rubber strip is the rubber strip after the simulated working condition of Example 6.
[0068] right Figure 1 and Figure 2 An appearance inspection of the rubber strips revealed that the shapes of 1# and 2# rubber strips and 11# to 16# rubber strips were standard cylinders, without obvious macroscopic deformation, with uniform white color and smooth surface; the shape of 3# rubber strip was an irregular square with cracks on the surface; the shape of 4# rubber strip was an irregular square with irregular undulations on the surface; the shapes of 5# to 10# rubber strips were irregular square with no cracks, pits or undulations on the surface; typical aging holes existed in the cross-sections of 3# to 10# rubber strips.
[0069] Example 8
[0070] This embodiment provides the performance of each rubber strip.
[0071] (1) Hardness analysis
[0072] The rubber strips were tested for Shore hardness. From the hardness test results, it can be seen that the Shore hardness values of 11# to 16# rubber strips have not changed much compared with the new rubber strips, while the Shore hardness values of 3# to 10# rubber strips are significantly greater than those of 11# to 16# rubber strips, indicating that the aging degree of 3# to 10# rubber strips is significantly greater than that of 11# to 16# rubber strips. The test results are also consistent with the actual use time of the samples. The results of the rubber strip hardness measurement are shown in Table 1.
[0073] Table 1: Rubber strip hardness measurement results (Shore A hardness)
[0074]
[0075]
[0076] (2) Density analysis
[0077] The density of the rubber strips was tested. From the results of the density test, it can be seen that the density values of 11#~16# rubber strips have not changed much compared with the new rubber strips, and the density values of 3#~10# rubber strips are significantly greater than those of 11#~16# rubber strips, indicating that the material of 3#~10# rubber strips has changed significantly after use, and the organic components in the material have volatilized to a large extent, which is consistent with the results of aging holes in the macroscopic inspection of 3#~10# rubber strips. The results of the rubber strip density measurement are shown in Table 2.
[0078] Table 2: Strip density measurement results (g / cm 3 )
[0079]
[0080]
[0081] (3) Analysis of tearing performance
[0082] The tearing performance test of the rubber strips shows that the elongation at break of 3#~10# rubber strips is significantly lower than that of 11#~16# rubber strips, indicating that the material of 3#~10# has aged significantly after use, and the aging has caused the elongation at break performance of the material to degrade; the elongation at break of 11#~16# rubber strips has also decreased to a certain extent compared with the new rubber strips, indicating that the performance of 11#~16# rubber strips has also begun to decline. The tearing performance test results of the rubber strips are shown in Table 3.
[0083] Table 3: Test results of rubber strip tearing performance
[0084]
[0085] (4) Volume change rate analysis
[0086] According to the measurement results of the rubber strip interface dimensions, the volume change rate of each rubber strip is estimated. The volume value of the new rubber strip is the average value of the 1# and 2# rubber strips. The volume value is calculated based on the unit length of 1. The calculation formula is as follows:
[0087] △V=100%×(Vi-V0) / V0;
[0088] Vi—volume value of new rubber strip;
[0089] V0—Volume of the adhesive strip after use.
[0090] Table 4: Volume change rate measurement results
[0091]
[0092]
[0093] From the value of the volume change rate, it can be seen that the volume of the rubber strip after use has changed significantly compared with the volume of the new rubber strip, the volume has increased, and obvious swelling has occurred. The volume change rate of 3#~10# rubber strips is significantly greater than that of 11#~16# rubber strips, indicating that the swelling phenomenon of 3# to 10# rubber strips after use is more obvious; the volume change rate of 11#~16# rubber strips is not obvious compared with the new rubber strips. According to the volume change trend of the rubber strips, it can be inferred that the longer the use time, the more obvious the swelling phenomenon.
[0094] (5) Thermal aging performance analysis
[0095] In order to verify whether the aging of the rubber strip is mainly caused by thermal factors and to evaluate the service life of the rubber strip at different temperatures, the thermal aging performance of the rubber strip was studied by using the accelerated aging test method to obtain the influence of different aging temperatures and aging times on the mechanical properties of silicone rubber. The calculation model in GB / T27800-2011 "Rapid Prediction Method for Service Life of Static Sealing Rubber Products" was used to predict the service life of silicone rubber in a hot air aging environment.
[0096] In this test, the elongation at break was selected as the aging performance index. According to GB / T20028-2005 "Estimation of service life and maximum operating temperature of vulcanized rubber or thermoplastic rubber using Arrhenius diagram", the performance attenuation of 50% (i.e., elongation at break EAB / % < 50% of the original value) was used as the failure index. Based on the aging model and combined with the failure index, the thermal aging life of the rubber strip was evaluated.
[0097] Through calculation, when the elongation at break is used as the service life indicator for estimating the service life of the rubber strip, the service life of the silicone rubber of this specification is shown in Table 5.
[0098] Table 5: Service life
[0099] Service life at 85°C Example 1 110 Example 2 108 Example 3 107 Example 4 80 Example 5 72 Example 6 73
[0100] At the normal use temperature of 85°C, the service life of the rubber strip can reach 107 to 110 years. Therefore, it can be concluded that the rubber strip has excellent heat resistance.
[0101] (6) Microscopic surface morphology analysis of rubber strips
[0102] Using a scanning electron microscope (SEM) to observe the microscopic surface morphology of each rubber strip, it can be seen that the surface of the 11# rubber strip is uniform, without cracks or holes; clear deep cracks can be seen under the scanning electron microscope on the 3# rubber strip, which is caused by the breakage of the rubber polymer chain, a typical manifestation of rubber aging, and consistent with the infrared cracking phenomenon of the 3# rubber strip; the cracks in the 5# rubber strip start from the side of the rubber strip and expand inward in a fatigue manner. The microscopic morphology of some rubber strips can be seen Figures 3 to 5 shown.
[0103] As described above, the present invention can be well implemented. The above embodiments are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various changes and improvements made to the technical solutions of the present invention by ordinary technicians in this field should fall within the protection scope determined by the present invention.
Claims
1. A rubber resistant to lubricating medium of steam turbine generator for nuclear power, characterized in that: The raw materials for preparing the rubber are hydrogenated nitrile, a vulcanization activator, stearic acid, an antioxidant, a plasticizer, an anti-wear agent, a silane coupling agent, a vulcanizing agent, an accelerator, ultra-short aramid fibers and an alkyl phenolic resin.
2. The rubber for nuclear power generation resistant to lubricating medium of steam turbine generator according to claim 1, characterized in that: The raw materials for preparing the rubber are composed, by weight, of 100 parts of hydrogenated nitrile, 2 to 12 parts of a vulcanizing activator, 0.5 to 2 parts of stearic acid, 0.5 to 4 parts of an antioxidant, 2 to 10 parts of a plasticizer, 5 to 25 parts of an anti-wear agent, 0.5 to 2 parts of a silane coupling agent, 4 to 10 parts of a vulcanizing agent, 0.8 to 2.5 parts of an accelerator, 0.5 to 4 parts of ultra-short aramid fibers and 0.5 to 3 parts of an alkylphenol-formaldehyde resin.
3. The rubber for nuclear power generation resistant to lubricating medium of steam turbine generator according to claim 1, characterized in that: The length of the ultra-short aramid fiber is no longer than 3 mm.
4. The rubber for nuclear power generation resistant to lubricating medium of steam turbine generator according to claim 3, characterized in that: The ultra-short aramid fiber is surface-modified by a diterpene quinone compound.
5. The rubber for nuclear power generation resistant to lubricating medium of steam turbine generator according to claim 4, characterized in that: The diterpene quinone compound is danshenxinone.
6. The rubber for nuclear power generation resistant to lubricating medium of steam turbine generator according to claim 1, characterized in that: The vulcanization activator is selected from at least one of zinc oxide and magnesium oxide; The antioxidant is selected from at least one of antioxidant MB, phenylenediamine antioxidants, and quinoline antioxidants; The anti-wear agent is selected from at least one of carbon black, montmorillonite, aluminum hydroxide, calcium carbide and microcrystalline wax; The silane coupling agent is selected from at least one of silane coupling agent A172, silane coupling agent A171, and silane coupling agent A151; The vulcanizing agent is vulcanizing agent DCP; The accelerator is TAIC.
7. A method for preparing the rubber resistant to lubricating medium of steam turbine generator for nuclear power according to any one of claims 1 to 6, characterized in that: include: The silane coupling agent, the ultra-short aramid fiber and the alkyl phenolic resin are mixed under pressure and heating to obtain a mixture; Hydrogenated nitrile, vulcanizing activator, stearic acid, antioxidant, plasticizer, anti-wear agent, the mixture, vulcanizing agent and accelerator are sequentially added for mixing, and after multiple thin passes, the lower sheet is cooled to obtain the product.
8. The preparation method according to claim 7, characterized in that: The ultra-short aramid fibers are surface-modified with diterpene quinone compounds before being made into the mixture; The surface modification comprises: immersing the ultra-short aramid fiber in a diterpene quinone compound, heat-treating the fiber at 40-60° C. for 6-12 hours, taking the fiber out, washing it with anhydrous ethanol, and drying it at room temperature.
9. The preparation method according to claim 7, characterized in that: The pressurized heating mixing comprises: mixing the silane coupling agent, the ultra-short aramid fiber and the alkyl phenolic resin at a pressure of 0.05-0.5 MPa and a temperature of 90-120° C.
10. The preparation method according to claim 7, characterized in that: The mixing parameters are: roller temperature 60°C-80°C, mixing roller distance 4-5mm; The parameters of the thin pass are: the thin pass roller distance is 0.5-1mm, and the thin pass is 20 times.